Policy Innovation of Smart Environment by the Recycling Project Method at the Samarinda City Environment Service - Einsbie Grata Myn; Adji Zahra Salsabila (Formosa Journal of Applied Sciences, 2022)
This study was conducted to determine the policy of the Samarinda City Environmental Service regarding the cleanliness of public roads from dirt or dust to Smart Environment. This study was conducted using a descriptive approach using a purposive sampling sample at the Samarinda City Environmental Service. Data analysis using the latest interactive data model as defined by Miles and Hubermans. The results of the study can be concluded that policies have been implemented by the City of Samarinda Environment Service such as using roadsweeper trucks which are fine sand suction devices and policy innovation is needed with the recycling project method to increase public interest and concern.